2015
DOI: 10.1097/md.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Relative Wall Thickness Versus Left Ventricular Mass Index in Non-Cardioembolic Stroke Patients

Abstract: In non-cardioembolic stroke patients, the cardiac manifestations of high blood pressure are of particular interest. Emerging data suggest that echocardiographically determined left ventricular hypertrophy is independently associated with risk of ischemic stroke.The primary objective of this study was to evaluate the frequency of different patterns of left ventricular (LV) remodeling and hypertrophy in a group of consecutive patients admitted with non-cardioembolic stroke or transient ischemic attack (TIA). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
(21 reference statements)
0
15
0
1
Order By: Relevance
“…9 The presence of only abnormal RWT is defined as concentric cardiac remodeling, 6 associated with adverse cardiovascular outcomes. 10,17,18 Thus, it is inferred that statistical significance in the association between abnormal RWT and eGFR of 60-89 mL/min/1.73 m 2 is maintained even after adjustment for hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The presence of only abnormal RWT is defined as concentric cardiac remodeling, 6 associated with adverse cardiovascular outcomes. 10,17,18 Thus, it is inferred that statistical significance in the association between abnormal RWT and eGFR of 60-89 mL/min/1.73 m 2 is maintained even after adjustment for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that men with mildly decreased renal function have an accompanying increased risk of concentric remodeling reflected by abnormal RWT. Given that concentric remodeling is linked to fatal cardiovascular outcomes such as stroke, myocardial infarction and heart failure, 10,17,18 it is postulated that men with mildly decreased renal function have worse cardiovascular prognosis compared with men with normal renal function. These results may provide additional information lacking in previous studies that have evaluated the association between renal function and LV geometry change.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of LV fractional shortening and LV mass (g) were calculated as [(EDD − ESD)/EDD] × 100 and 0.8(1.04[([LVEDD + IVSd + PWd] 3 − LVEDD 3 )]) + 0.6 respectively. Normalized LV mass was calculated as LV mass (mg)/body weight (g) 50 , 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the two-dimensional echocardiographic measurements, the left ventricular mass index (LV Mass index) was calculated with a validated method [39], the relative wall thickness (RWT) of the left ventricle (LV) was calculated as (2× posterior wall thickness)/LVedd [39], and the left atrial volume index (LAVI) was obtained with a validated method for each participant [40].…”
Section: Participants Visitmentioning
confidence: 99%